Ewolucja stanowiska Polski wobec Wspólnej Polityki Bezpieczeństwa i Obrony Unii Europejskiej - Stolarczyk, Mieczysław (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Evolution of Polish position towards European Union Common Security and Defence Policy The objective of this article is to present the evolution of Polish government position towards CSDP. The author points out the main stages of the Polish government attitude towards CSDP that were shaped by the consecutive governments. The author indicates that since 1999, when the CSDP was created, the position of Polish government has been changing from a very reserved or critical one to an opened approval and major involvement in the CSDP development. In author’s opinion, there are three stages in regard to Polish position towards CSDP and the European Security and Defence Identity (ESDI) that led to CSDP creation. First stage dates back to 1990s and is related to ESDI and the way the European Union countries tried to implement its objectives; second one takes place between 1999 and 2004, when the CSDP was created and when Poland was participating in adhesion talks; third one, between 2004 and 2014, is characterized by a growing Polish support for the CSDP and stronger engagement of consecutive governments in the development of this process. Nonetheless, it should be mentioned that the CSDP has never been a priority in the Polish security policy. Key words: evolution of government position, security police, defence, support and engagement